2022
DOI: 10.3389/fmicb.2022.1033158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of host genotype in establishing root associated microbiome of indica rice cultivars for plant growth promotion

Abstract: Rice plants display a unique root ecosystem comprising oxic-anoxic zones, harboring a plethora of metabolic interactions mediated by its root microbiome. Since agricultural land is limited, an increase in rice production will rely on novel methods of yield enhancement. The nascent concept of tailoring plant phenotype through the intervention of synthetic microbial communities (SynComs) is inspired by the genetics and ecology of core rhizobiome. In this direction, we have studied structural and functional varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 125 publications
(133 reference statements)
1
3
0
Order By: Relevance
“…The growth and development of different blueberry cultivars were enhanced by recruiting specific rhizosphere microflora based on genotype ( Jacoby et al, 2017 ). Our results showed that the different genotypes of cotton recruited specific rhizosphere microbiomes, suggesting that the rhizosphere microbial community was regulated by host genotypes, consistent with the results in soybean, rice, and barley ( Bulgarelli et al, 2015 ; Singh et al, 2022 ; Qu et al, 2023 ). In addition, resistant cultivars may resist pathogen invasion by enriching specific bacterial or fungal groups in the rhizosphere ( Mendes et al, 2017 ; Kwak et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…The growth and development of different blueberry cultivars were enhanced by recruiting specific rhizosphere microflora based on genotype ( Jacoby et al, 2017 ). Our results showed that the different genotypes of cotton recruited specific rhizosphere microbiomes, suggesting that the rhizosphere microbial community was regulated by host genotypes, consistent with the results in soybean, rice, and barley ( Bulgarelli et al, 2015 ; Singh et al, 2022 ; Qu et al, 2023 ). In addition, resistant cultivars may resist pathogen invasion by enriching specific bacterial or fungal groups in the rhizosphere ( Mendes et al, 2017 ; Kwak et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have noted mixed results on the association between host plant diversity and overall diversity of microbes in their rhizospheres. For example, Zverev et al ( 2021 ) did not find a correlation between alpha diversity of plants and rhizosphere bacteria in farmed and fallow fields, but Singh et al ( 2022 ) reported that alpha diversity varied among rice cultivars. These studies suggest a complex interplay of factors likely determine the level of microbial diversity associated with plants, as well as the specific types of microbes present.…”
Section: Discussionmentioning
confidence: 99%
“…Geography and host genotype could have major influences on the microbiome the fungus encounters as different rice genotypes have been found to have different microbiomes ( Xiong et al . 2021 ; Singh et al . 2022 ; Zhang et al .…”
Section: Discussionmentioning
confidence: 99%